2007
DOI: 10.1128/aem.02420-06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein, Polysaccharide, and Oxygen Concentration Profiles on Biofilm Cohesiveness

Abstract: It is important to control biofilm cohesiveness to optimize process performance. In this study, a membraneaerated biofilm reactor inoculated with activated sludge was used to grow mixed-culture biofilms of different ages and thicknesses. The cohesions, or cohesive energy levels per unit volume of biofilm, based on a reproducible method using atomic force microscopy (F. Ahimou, M. J. Semmens, P. J. Novak, and G. Haugstad, Appl. Environ. Microbiol. 73:2897-2904, 2007), were determined at different locations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(85 citation statements)
references
References 36 publications
3
82
0
Order By: Relevance
“…Quantification of cohesion is important for understanding biofilm biology, and such data are crucial for modeling and forecasting biofilm development so that better control strategies can be developed (55). Previous studies of biofilm cohesiveness have characterized it as highly stratified (3,4,18,43), influenced by ionic strength (14,34), proportional to shear rate (37), and often variable over 3 orders of magnitude (40,50). Although an earlier study by Spiers and Rainey (48) provided semiquantitative measurements of the role of LPS on bacterial cohesion within a biofilm, a truly quantitative account of the effect of LPS on biofilm cohesion has not been demonstrated.…”
mentioning
confidence: 99%
“…Quantification of cohesion is important for understanding biofilm biology, and such data are crucial for modeling and forecasting biofilm development so that better control strategies can be developed (55). Previous studies of biofilm cohesiveness have characterized it as highly stratified (3,4,18,43), influenced by ionic strength (14,34), proportional to shear rate (37), and often variable over 3 orders of magnitude (40,50). Although an earlier study by Spiers and Rainey (48) provided semiquantitative measurements of the role of LPS on bacterial cohesion within a biofilm, a truly quantitative account of the effect of LPS on biofilm cohesion has not been demonstrated.…”
mentioning
confidence: 99%
“…This pattern is very similar to that of the total biomass (PLFAs). A previous study indicated that biofilm cohesiveness was strongly correlated with biofilm polysaccharide content, which increased with the thickness but not with the age of the biofilm (Ahimou et al, 2007). From figure 4, the total polysaccharide of emitter A is much more than that of emitter B, especially in the period from 96 h to 144 h. This suggests that the design of emitter A may result in less flow shearing force, allowing for more biofilm development and thus resulting in emitter A clogging more rapidly.…”
Section: Influence Of Biomass Accumulation On Emitter Clogging Degreementioning
confidence: 99%
“…The spatial distribution of EPS was determined using the fluorescent intensity data from CLSM microscopy with multiple fluorescent stains, as shown in Figure 2d-j. The EPS are considered to be high MW mixtures (containing proteins, polysaccharides, nucleic acids, and lipids) created by the lysis of microorganismal cells, which tend to adhere to the cell surfaces and enhance protection against an unfavorable external environment [43,44]. The concentration and composition of EPS may differ under different growth conditions that determine the internal cohesive or adhesive strengths.…”
Section: Characterization Of Aerobic Granular Sludgementioning
confidence: 99%